Morphological and molecular characteristics of Donax incarnatus (Bivalvia: Donacidae) from Badur Beach, Madura Island, Indonesia based on the COX1 gene - CATHERINE BERLIANA WIJAYA; RENI AMBARWATI; DWI ANGGOROWATI RAHAYU (Society for Indonesian Biodiversity, 2023)
Abstract. Wijaya CB, Ambarwati R, Rahayu DA. 2023. Morphological and molecular characteristics of Donax incarnatus (Bivalvia: Donacidae) from Badur Beach, Madura Island, Indonesia based on the COX1 gene. Biodiversitas 24: 2805-2813. Donacidae, a family of marine bivalve mollusks, has a high diversity of morphological traits, including shape and color pattern variations. However, these variations often led to errors in morphological identification, necessitating the use of molecular identification methods for accurate species identification and support. This study aims to analyze the morphological and molecular characteristics of Donax incarnatus Gmelin, 1791 collected from Badur Beach of Madura Island, Sumenep District, East Java Province, Indonesia, using the COX1 gene as a molecular marker. Morphological characterization was conducted through qualitative and quantitative observations, while sequencing results were analyzed using bioinformatics software. The results showed that the exterior color of D. incarnatus has three morphological variations, namely purple-black (OQ692130.1), yellowish orange (OQ692131.1), and white (OQ692132.1). Molecular characterization indicated that the similarity value of D. incarnatus with these variations ranged from 96.06% to 99.61%. At the same time, the alignment results of all samples with reference species and outgroups obtained five variations of nucleotide bases. The average genetic distance between D. incarnatus and the in group was 0.01. The phylogenetic tree results obtained using Neighbor-Joining (NJ) and Maximum Likelihood (ML)methods were categorized into two subclusters: D. incarnatus species from Thailand and the study sample from Badur Beach, Madura Island, Indonesia, were placed in the same cluster.